Kinerja Aparatur Sipil Negara Ditinjau dari Self-Efficacy dan Lingkungan Kerja Fisik di Kabupaten X - Dea Yuspita Sary; Dian Febriany Putri (Journal of Social, Culture, and Language, 2024)
Performance is the real behavior shown by each person as a work achievement produced in accordance with their role. In order to achieve good performance of the State Civil Service, self-efficacy and a physical work environment are needed. The research aims to determine the influence of self-efficacy and the physical work environment on the performance of State Civil Apparatus in X Regency. Researchers distributed online questionnaires to 132 State Civil Servants in X Regency, with 54 men and 78 women. The scales used are the Individual Work Performance Questionnaire (IWPQ), General Self-Efficacy Scale (GSES), and Reactions Physical Work Environment Scale (RPWES). This research uses quantitative methods. The research results show that self-efficacy and the physical work environment simultaneously have a positive effect on the performance of the State Civil Service in X Regency. Keywords: Performance, Self-Efficacy, Physical Work Environment